Pelatihan Akuntansi sebagai Upaya Meningkatkan Kompetensi Akuntansi Pelaku Usaha Mikro Kecamatan Prambon Kabupaten Nganjuk - Linawati, Linawati; Winarko, Sigit Puji; Nurdiwaty, Diah; Riswahyuning, Mareta Selvia; Sari, Meilinda Trinita (Universitas Nusantara PGRI Kediri, 2024)
As micro businesses develop today, human resource capabilities in management and recording should be followed. However, in reality there are still many micro businesses that are not able to provide good accounting records of their activities. This problem also occurs in micro businesses in Prambon District under the guidance of the Nganjuk Regency Cooperatives and Micro Enterprises Service. This community service activity aims to provide knowledge and understanding of accounting to micro business actors assisted by the Nganjuk Regency Cooperatives and Micro Enterprises Service, in the form of accounting training. The material presented includes accounting records, financial reports, COGS and BEP. The activity was carried out on August 30 2023, which was attended by 30 micro business actors in Prambon District. The methods used are lectures, demonstrations and questions and answers. The aim of the service activity is to provide knowledge and understanding to micro business actors in Prambon District assisted by the Nganjuk Regency Cooperative and Micro Business Service regarding accounting and training in preparing financial reports which has shown success. This can be seen from the results of the performance given to participants to calculating COGS and BEP with good and correct results, as well as being able to record business transactions and prepare financial reports. The criteria for achievement are also shown in the participants' enthusiasm during the activity from start to finish as well as the results of their work.